Disciplinary literacy instructions on writing scientific explanations: a case study from a chemistry classroom in an all-girls school - Putra, G.; Tang, Kok-Sing (R S C Publications, 2016)
This paper is a case study that reports on findings from a design-based research with the purpose of helping secondary school chemistry students in an all-girls school develop the ability to construct scientific explanations – an important literacy skill in learning science. A series of lessons on the topic of chemical bonding was designed to explicitly teach the three-part structure often found in the genre of scientific explanations and provide opportunities for students to apply the structure. The lesson series was observed and the students' worksheets and test papers were collected and analysed. The analysis of the structure of the students' written scientific explanations was done through genre analysis. Most of the students were found to be able to write well-structured scientific explanations addressing the topic of chemical bonding but only a fraction of them could re-contextualise the explanation structure.